BASIC PSYCHOLOGICAL NEED IS EFFECTIVE AS A MEDIATOR IN IMPROVING THE RELATIONSHIP BETWEEN SCHOOL CLIMATE AND STUDENT ENGAGEMENT IN ELEMENTARY SCHOOL STUDENTS - Ainun Latifa; Mardianto Mardianto (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2024)
This study aims to see how the contribution of school climate and the fulfillment of basic psychological needs to student engagement in elementary school students in Agam district.  This study uses quantitative methods. Student engagement was measured using School Engagement Measure (SEM)- MacArthur with a reliability of 0.869, Comprehensive School Climate Inventory with a reliability of 0.860, and Basic Psychological Needs in the Classroom Scale (BPN-CS) with a reliability of 0.832. The sampling technique in this study used cluster random sampling with a total of 138 elementary students in Agam district. Multiple linear regression analysis is the analytical technique used in this study. The results of this study showed a significance value (p) of 0.00 <0.05, these results indicate that school climate and basic psychological needs simultaneously contribute to student engagement in elementary school students in Agam district. The contribution given is as much as 49.7%. School climate and basic psychological need separately also show a contribution to student engagement, and school climate shows a higher contribution than basic psychological need